Physical activity and executive function in Chinese preschool children: the mediating role of sleep problems - Chen, Xiaolong; Li, TianChang; Zhou, Weiling; Huang, Lancheng; Zhang, Sanhua (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to examine the relationship between physical activity and executive function in preschool children, with a particular focus on the mediating role of sleep problem.MethodsA total of 159 preschool children participated in this study. Physical activity levels were objectively measured using the ActiGraph GT3X-BT. Sleep problems and executive function were assessed using the Chinese versions of the Children’s Sleep Habits Questionnaire and the Behavior Rating Inventory of Executive Function-Preschool Version. Statistical analyses including correlation and mediation analyses were conducted using SPSS 29.0 and Mplus 8.0.Results(1) Light physical activity (LPA) (r = −0.53, p < 0.01), moderate-to-vigorous physical activity (MVPA) (r = −0.61, p < 0.01), and total physical activity (TPA) (r = −0.64, p < 0.01) showed significantly negatively correlated with executive function scores. (2) LPA (r = −0.27, p < 0.01), MVPA (r = −0.29, p < 0.01), and TPA (r = −0.31, p < 0.01) were significantly negatively correlated with sleep problems. (3) Sleep problems were significantly positively correlated with executive function scores (r = 0.47, p < 0.01). (4) Sleep problems mediated 24.65–28.20% of the effects of LPA, MVPA, and TPA on executive function.ConclusionHigher levels of LPA, MVPA, and TPA were significantly associated with better executive function and fewer sleep problems in preschool children. Sleep problems play a partial mediating role in the relationship between physical activity and executive function. These findings suggest that preschool educators and parents should implement appropriate physical activity interventions to improve sleep health, ultimately fostering optimal executive function development in young children.